Unexpected ovarian malignancy after conservative laparoscopic surgery: ﬁve case series in a half decade of experience - Abd. Wahab, Noraziana; Chalermchockchareonkit, Amphan; Chaisilwattan, Pongsakdi; Mustafa, Kamarul Bahyah (Springer Verlag, 2012)
Aims To analyse and describe cases of unexpected ovarian malignancy after conservative laparoscopic surgery for an apparent benign ovarian mass at our centre. Methods This retrospective study was performed by collecting data from records of premenopausal women who underwent conservative laparoscopic surgery for benign ovarian mass at Siriraj Hospital over a 5 year period from 2006 to 2010. The rate of unexpected malignancy, histopathological type of the ovarian neoplasm and follow-up after surgery were reviewed. Results During the study period, 1,161 patients underwent conservative laparoscopic surgery. Of these, ﬁve (0.43%) had ovarian malignancy which were diagnosed after reviewing histopathological report postoperatively. The histopathological diagnosis was borderline tumour in two patients, clear cell carcinoma, granulosa cell tumour and mucinous cell adenocarcinoma in the other three patients. All patients are alive after a mean follow-up of 9–60 months with two patients developed recurrence. Conclusion The main concern for laparoscopic management of ovarian masses is unexpected malignancy. However, with careful patient selection, proper technique and an experienced operator, laparoscopic treatment of ovarian masses is the best approach and should be implemented, with low risk of unexpected malignancy and recurrence.